Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China - Li, Hongxing; Yang, Lin; Chen, Xiangsheng (Zootaxa, 2019)
Two new species of the bamboo-feeding genus Arcofacies Muir, A. longispinus sp. nov. and A. varius sp. nov., are described and illustrated from southwest China (Yunnan). A checklist to the species of Arcofacies is provided as well as a key for the Chinese species.